2016
DOI: 10.1186/s40478-016-0343-2
|View full text |Cite
|
Sign up to set email alerts
|

LRP1 expression in microglia is protective during CNS autoimmunity

Abstract: Multiple sclerosis is a devastating neurological disorder characterized by the autoimmune destruction of the central nervous system myelin. While T cells are known orchestrators of the immune response leading to MS pathology, the precise contribution of CNS resident and peripheral infiltrating myeloid cells is less well described. Here, we explore the myeloid cell function of Low-density lipoprotein receptor-related protein-1 (LRP1), a scavenger receptor involved in myelin clearance and the inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 50 publications
4
71
0
Order By: Relevance
“…Consistent with the study by Chuang et al in macrophage [51], our current study also found that LRP1 down-regulation in primary microglia not only leads to NF-κB activation in the absence of inflammatory stimuli but also enhances the LPS-induced NF-κB activity. Gaultier et al has described a potential mechanism through which LRP1 may suppress NF-κB activation in mouse macrophage.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the study by Chuang et al in macrophage [51], our current study also found that LRP1 down-regulation in primary microglia not only leads to NF-κB activation in the absence of inflammatory stimuli but also enhances the LPS-induced NF-κB activity. Gaultier et al has described a potential mechanism through which LRP1 may suppress NF-κB activation in mouse macrophage.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, recent work by Chuang et al demonstrated that in the brains of microglial Lrp1 conditional knockout mice, microglia adopt a pro-inflammatory phenotype characterized by amoeboid morphology, indicating that LRP1 may regulate microglial activation in vivo. Of note, their work also suggests that ablation of LRP1 in microglia, not in macrophage, had a significant impact on the disease severity of multiple sclerosis [51]. However, the regulation and function of LRP1 as well as related signaling pathways in microglia remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active EAE was performed as described previously (16). Briefly, male or female (sex-matched within experiments) C57BL/6 mice were immunized subcutaneously with 50 μg of myelin oligodendrocyte glycoprotein peptide 35–55 (MOG 35–55 ) (CSBIO #CS0681) emulsified at a 1:1 ratio in Complete Freud’s Adjuvant (Sigma Aldrich #F5881).…”
Section: Methodsmentioning
confidence: 99%
“…Modulating phagocytosis may also contribute to LRP1's 80 previously described role in mediating an anti-inflammatory effect on microglia during EAE 176 .…”
Section: Introductionmentioning
confidence: 91%